The politics of promoting gender equity in contemporary Uganda: Cases of the Domestic Violence Law and the policy on Universal Primary Education - Ahikire, Josephine; Mwiine, Amon A. (ESID, 2015)
The paper looks at the ways in which power and politics shape the realisation of women’s rights and gender equity in Ugandan state policy adoption and implementation. The key question explored is around the nature of political power and its influence on gender policy incentives in terms of adoption and implementation. The argument is structured around the politics of recognition – recognition referring to what has been made possible in the form of gender-sensitive policy outcomes, the incentives for the different courses of action, and what influences the ability of the political system to channel women’s interests and representation into effective policy formulation and implementation. This question is explored by investigating the progress of two policy agendas, namely the Domestic Violence Act of 2010 and the promotion of girls’ education within the Universal Primary Education (UPE) policy instituted in 1997.
Keywords: women; political settlement; gender equity; policy incentives; patronage; Uganda